Cognitive-behavioral therapy to miscarriage: results from the use of a grief therapy protocol (Archives of Clinical Psychiatry, 2011)
BACKGROUND: The grieving process due to a fetal loss has several features which should be considered in the clinical care of patients going through a miscarriage experience. Bereaved patients present greater demands for medical assistance, number of hospitalizations and are more vulnerable to psychosomatic problems than the general population. OBJECTIVE: This paper aims to present a case report of miscarriage grief treated with a cognitive behavioral therapy protocol. METHOD: The therapy was composed by 12 sessions and the protocol involves the development of strategies to deal with the main somatic complaints, learning of new abilities, approach to cognitive and emotional alterations and training to handle behavioral problems. Results were evaluated by Beck Anxiety Inventory, Beck Depression Inventory, Beck Hopelessness Scale, and Goldberg's General Health Questionnnaire (GGHQ). RESULTS: Patient presented reduction in depressive and anxiety symptoms. Hopelessness also decreased. All the GGHQ factors presented reduction, with a marked decline in "desire of death" and "psychosomatic disorders". It was also noted an improvement in sleep quality. DISCUSSION: The treatment showed itself effective in relation to the factors presented, apart from collaborating for a better quality of life and facilitating the social reinsertion of the patient.